Percutaneous Transvenous Mitral Commissurotomy: In-hospital Outcome of Patients with Mitral Stenosis (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 24-28 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13548